PENGARUH RISK PROFILE, KOMITE AUDIT, DAN CAPITAL TERHADAP FINANCIAL DISTRESS - Nicholaus Raymond Widiyanto; Patricia Febrina Dwijayanti (Universitas Katolik Widya Mandala Surabaya, 2022)
One condition that is not desired by all companies is financial distress, which is a condition where the company is on the verge of bankruptcy. Many factors affect financial distress, so this study aims to examine the effect of risk profile, audit committee and capital on financial distress. This research was conducted on 40 banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Financial distress is measured using Altman Z-Score Modification. The independent variables in this study were proxied by NPL, LDR, Audit Committee Size, and CAR. This study also uses the control variable company size as a proxy for total assets and profitability as a proxy for ROA. The results of this study indicate that NPL and LDR have no effect on financial distress, while the audit committee and capital have an influence on financial distress..